Validation of the ISTH/SSC bleeding assessment tool for inherited platelet disorders: A communication from the Platelet Physiology SSC - Gresele, Paolo; Orsini, Sara; Noris, Patrizia; Falcinelli, Emanuela; Alessi, Marie Christine; Bury, Loredana; Borhany, Munira; Santoro, Cristina; Glembotsky, Ana C.; Cid, Ana Rosa; Tosetto, Alberto; De Candia, Erica; et al. (Journal of thrombosis and haemostasis, 2020)
Background Careful assessment of bleeding history is the first step in the evaluation of patients with mild/moderate bleeding disorders, and the use of a bleeding assessment tool (BAT) is strongly encouraged. Although a few studies have assessed the utility of the ISTH‐BAT in patients with inherited platelet function disorders (IPFD) none of them was sufficiently large to draw conclusions and/or included appropriate control groups. Objectives The aim of the present study was to test the utility of the ISTH‐BAT in a large cohort of patients with a well‐defined diagnosis of inherited platelets disorder in comparison with two parallel cohorts, one of patients with type‐1 von Willebrand disease (VWD‐1) and one of healthy controls (HC). Patients/Methods We enrolled 1098 subjects, 482 of whom had inherited platelet disorders (196 IPFD and 286 inherited platelet number disorders [IT]) from 17 countries. Results IPFD patients had significantly higher bleeding score (BS; median 9) than VWD‐1 patients (median 5), a higher number of hemorrhagic symptoms (4 versus 3), and higher percentage of patients with clinically relevant symptoms (score > 2). The ISTH‐BAT showed excellent discrimination power between IPFD and HC (0.9 < area under the curve [AUC] < 1), moderate (0.7 < AUC < 0.9) between IPFD and VWD‐1 and between IPFD and inherited thrombocytopenia (IT), while it was inaccurate (AUC ≤ 0.7) in discriminating IT from HC. Conclusions The ISTH‐BAT allows to efficiently discriminate IPFD from HC, while it has lower accuracy in distinguishing IPFD from VWD‐1. Therefore, the ISTH‐BAT appears useful for identifying subjects requiring laboratory evaluation for a suspected IPFD once VWD is preliminarily excluded.